PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKn MENGGUNAKAN MODEL STAD DI KELAS V SEKOLAH DASAR - Rahmadani, Mona; Reinita, Reinita; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The aim of this research is to describe the improvement of students’ learning result in the civic subject by using the STAD Model for 5th grade students. The subjects of this research were the researcher herself and 20 students. This classroom action research used qualitative and quantitative approaches. The result shows that in planning phases there is improvement from 76,12 in cycle I to 93,5 in cycle II. Teachers’ aspect improves from 68,74 in cycle I to 91,66 in cycle II. students’ aspect improves from 68,74 in cycle I to 91,66 in cycle II. furthermore, the improvement also can be seen from students’ learning result that improves from 76,12 in cycle I to 93,5 in cycle II. Thus, it can be concluded that the implementation of the STAD Model can improve students’ learning result.    Keywords: PKn; Learning Outcomes; STAD Model